R&D Investment and Financing Constraints of Small and Medium-Sized Firm - Dirk Czarnitzki; Hanna L. Binz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This study tests for financial constraints on R&D investment and how they differ from capital investment. To identify constraints in the access to external capital, we employ a credit rating index. Our models show that internal constraints, measured by mark-ups, are more decisive for R&D than for capital investment. For external constraints, we find a monotonic relationship between the level of constriction and firm size for both types of investment. Thus, external constraints turn out to be more binding with decreasing firm size. On the contrary, we do not find such monotonic relationships for internal constraints. Differentiation by firms? age does not support lower constraints for older firms.
Keywords: O31; O32; 330; R&D Investment; Capital Investment; Financial Constraints; Panel Data; Censored Regression Models; Forschungsfinanzierung; Verschuldungsrestriktion; Industrielle Forschung; Investition; Kreditwürdigkeit; Deutschland